Factors Affecting the Incidence of Anemia in Pregnant Women at the Sawah Lebar Community Health Center in Bengkulu City in 2025 - Kintan Anissa; Mepi Sulastri (Utan Kayu Publishing, 2025)
Anemia in pregnant women remains a significant public health problem and contributes to an increased risk of pregnancy and childbirth complications. This study aims to determine the factors that influence the incidence of anemia in pregnant women at the Sawah Lebar Community Health Center in Bengkulu City. This study used a quantitative design with a cross-sectional approach. The sample consisted of 56 pregnant women selected using total sampling technique. Data were collected through hemoglobin level examination and questionnaires regarding nutritional status, parity, and compliance with iron tablet consumption. Data analysis was performed using univariate and bivariate analysis with chi-square test and odds ratio (OR) calculation.The results showed that some pregnant women had anemia. There was a significant relationship between nutritional status (p0.05), parity (p0.05), and compliance with iron tablet consumption (p0.05) and the incidence of anemia. Pregnant women with poor nutritional status, risky parity, and non-compliance with iron tablet consumption had a greater chance of developing anemia. It was concluded that nutritional status, parity, and compliance with iron tablet consumption are factors that influence the incidence of anemia in pregnant women. There is a need to improve nutrition education and monitor compliance with iron tablet consumption at community health centers to reduce the incidence of anemia in pregnant women.